IMPROVING THE EXCESS RETURN METHOD FOR THE PURPOSE OF BANK VALUATION - Matvey D. Bondarenko (Статистика и экономика)
The relevance of objective and precisebank valuation conduction has been steadily increasing in recent years. However, all existing valuation methods and models have some limitations to value a bank with a high degree of accuracy, simplicity and clarity. A modiﬁ ed version of the excess return valuation method that had been specially adapted for bankvaluation was proposed in the article. It isexpected that the proposed method will beused as a base for further development ofbank valuation tools and thus will signiﬁcantly enhance the competitiveness andefﬁciency of the banking system.